Implementasi Penguatan Karakter Profil Pelajar Pancasila untuk Meningkatkan Karakter Gotong Royong SDN 2 Kerso - Kusuma, Eka Satria Pandu; Muhaimin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
Character education is very important for the development of students. This study aims to examine the implementation of strengthening the character of the Pancasila Student Profile to enhance the spirit of mutual cooperation at SDN 2 Kerso. The method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Observations are conducted to monitor the mutual cooperation behavior of fifth grade students, while interviews with teachers aim to gather more detailed information about existing issues. The observation results indicate that instilling mutual cooperation values can be achieved through daily schedule programs, class picket activities, group assignments, as well as educational content and rewards. This strategy aims to motivate students to apply mutual cooperation behavior. Learning themes that support the strengthening of mutual cooperation character include subjects such as Civic Education, Indonesian Language, Arts and Culture, Mathematics, Social Studies, and Physical Education. Keywords: Character Education, Mutual Cooperation, Pancasila Student Profile